Multidisciplinary coordinated care of hereditary hemorrhagic telangiectasia (Osler–Weber–Rendu disease). (April 2023) - Alkhalid, Yasmine; Darji, Zeena; Shenkar, Robert; Clancy, Marianne; Dyamenahalli, Umesh; Awad, Issam A; ,
Hereditary hemorrhagic telangiectasia (HHT), also known as Osler–Weber–Rendu disease, is a rare disorder with a case prevalence as high as one in 5000, causing arteriovenous malformations in multiple organ systems. HHT is familial with autosomal dominant inheritance, with genetic testing allowing confirmation of the diagnosis in asymptomatic kindreds. Common clinical manifestations are epistaxis and intestinal lesions causing anemia and requiring transfusions. Pulmonary vascular malformations predispose to ischemic stroke and brain abscess and may cause dyspnea and cardiac failure. Brain vascular malformations can cause hemorrhagic stroke and seizures. Rarely, liver arteriovenous malformations can cause hepatic failure. A form of HHT can cause juvenile polyposis syndrome and colon cancer. Specialists in multiple fields may be called to care for one or more aspects of HHT, but few are familiar with evidence-based guidelines for HHT management or see a sufficient number of patients to gain experience with the unique characteristics of the disease. Primary care physicians and specialists are often unaware of the important manifestations of HHT in multiple systems and the thresholds for their screening and appropriate management. To improve familiarity, experience, and coordinated multisystem care for patients with HHT, the Cure HHT Foundation, which advocates for patients and families with this disease, has accredited 29 centers in North America with designated specialists for the evaluation and care of patients with HHT. Team assembly and current screening and management protocols are described as a model for evidence-based, multidisciplinary care in this disease.